STRATEGIES AND METHODS OF TEACHING VOCABULARY: A COMPREHENSIVE APPROACH - O‘ktamova N. N. (Bright Mind Publishing, 2025)
Vocabulary acquisition plays a fundamental role in the overall language learning process. A strong vocabulary is essential for communication, reading comprehension, and academic success. This article explores various strategies and methods of teaching vocabulary, emphasizing their effectiveness in diverse classroom settings. It reviews traditional approaches such as explicit instruction and contextual learning, modern task-based methods, and the integration of technology in vocabulary teaching. The cognitive processes involved in vocabulary acquisition are discussed, highlighting the importance of repetition, active engagement, and contextual usage for long-term retention. The article examines the role of learner motivation and individual differences in determining the success of vocabulary teaching methods. By analyzing contemporary research and practical classroom examples, this study provides educators with a range of strategies to enhance vocabulary instruction and better meet the needs of language learners.
Keywords: Vocabulary acquisition, language learning, teaching strategies, cognitive processes, task-based learning, technology integration, student engagement.